Propagation of Quercus incana by the Air-layering - Chandra, J. P.; Mahindru, J. L. (Indian Forester, 1977)
Quercus incana be propagated by air-layering. Untreated air-layers gave only 4 percent success but treatment with 1 part Rootone in 100 parts lanolin gave 28 percent success. It was also observed that, lower concentrations of root promoting hormone produced more rooted air layers and with better root development.